Stop-and-Restart Style Execution for Long Running Decision Support Queries - Chaudhuri, Surajit; Kaushik, Raghav; Pol, Abhijit; Ramamurthy, Ravi (VLDB, 2007)
Long running decision support queries can be resource intensive and often lead to resource contention in data warehousing systems. Today, the only real option available to the DBAs when faced with such contention is to carefully select one or more queries and terminate them. However, the work done by such terminated queries is entirely lost even if they were very close to completion and these queries will need to be run in their entirety at a later time. In this paper, we show how instead we can support a Stop-and-Restart style query execution that can leverage partially the work done in the initial query execution. In order to re-execute only the remaining work of the query, a Stop-and- Restart execution would need to save all the previous work. But this approach would clearly incur high overheads which is undesirable. In contrast, we present a technique that can be used to save information selectively from the past execution so that the overhead can be bounded. Despite saving only limited information, our technique is able to reduce the running time of the restarted queries substantially. We show the effectiveness of our approach using real and benchmark data.